2022
DOI: 10.3390/asi5040064
|View full text |Cite
|
Sign up to set email alerts
|

BIM-Based Method for the Verification of Building Code Compliance

Abstract: Urban planning is a valuable tool for growth control and city development, both to maintain the local urban identity and provide life quality for inhabitants. To regulate it, local governments have defined standards for a proper city’s growth through municipal and detailed urban plans. Such instruments identify a set of rules which constructions and buildings must fulfil for a careful and smooth integration within the urban areas. New projects are required to comply with such rules, and designers must adapt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The research findings also confirmed that the REVIT software could minimize much effort and time required by engineers to assess the budget related to challenging construction projects with higher complexity and components, like this case study. The results of this work are consistent with the research findings of [1][2][3][4], who stated that BIM technology and the REVIT software tool could minimize much of human errors and achieve a higher degree of precision. Also, these results are consistent with the findings of [5][6][7], who reported that the REVIT program could save considerable effort and time that would be significantly consumed by engineers to estimate the construction project cost.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The research findings also confirmed that the REVIT software could minimize much effort and time required by engineers to assess the budget related to challenging construction projects with higher complexity and components, like this case study. The results of this work are consistent with the research findings of [1][2][3][4], who stated that BIM technology and the REVIT software tool could minimize much of human errors and achieve a higher degree of precision. Also, these results are consistent with the findings of [5][6][7], who reported that the REVIT program could save considerable effort and time that would be significantly consumed by engineers to estimate the construction project cost.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the rising number of small-, medium-, and largescale construction projects worldwide, and because of the increasing rates of projects' complexity, the estimation process of the budget related to the construction project has become more complicated, effort, and time-consuming, and may contribute to a larger number of human errors [1][2][3][4]. The motivation of this research is reflected in the critical benefits, and substantial contributions of modern constriction techniques like Building Information Modeling (BIM) in helping civil engineers, quantity surveyors, designers, and planners calculate the volume of construction materials with higher degrees of accuracy, less human errors, less effort, and very low amount of time and cost required to make the materials quantity take-off.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen and Kim [24] developed a framework for a cooperative building design environment in which every participant in the project can monitor the code compliance status of their respective designs through the use of BIM technology. Villaschi et al [25] proposed a method based on BIM to streamline the verification procedure of code compliance in construction projects. Their findings provided a real-time decision support tool enabling designers to determine whether their buildings comply with local urban codes at any point in the design process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the SBTool PT Urban Guide, to calculate this indicator is necessary to sum the areas appropriately used according to their natural potential and make the ratio with the studied area. The requirements for land use and the properties of each area can be added to the digital model using Dynamo [29]. When the areas are defined in the model, a Dynamo routine can be performed for calculation [30].…”
Section: The Indicator To Measure the Used Natural Potential Of Landmentioning
confidence: 99%